40Ar-39Ar ages and petrogenesis of middle Eocene post-collisional volcanic rocks along the Izmir-Ankara-Erzincan suture zone, NE Turkey. (15th April 2019) - Göçmengil, Gönenç; Karacık, Zekiye; Genç, Ş. Can; Prelević, Dejan; Billor, Zeki
Graphical abstract: Highlights: Two different middle Eocene volcanic episodes studied in terms of petrology and geochronology. Relationship of mantle metasomatism and alkaline volcanism revealed. Magma genesis in post-collisional setting controlled by melting of veined metasomatized peridotitic mantle. Assimilation, fractional crystallization and magma mixing coevally operated during magmatism. Abstract: The central and northeastern of Turkey were shaped by the transition from collisional to post-collisional tectonics and coeval magmatism during Early Cenozoic. However, the temporal and spatial evolution of the magmatism during the middle Eocene remains elusive. In this paper, we provide petrological, isotopic and radiometric data from two middle Eocene volcano-sedimentary successions, from the northern (Almus) and southern (Yıldızeli) parts of the Izmir–Ankara–Erzincan Suture Zone, and discuss their generation in the post-collisional setting. Our results indicate that the volcanic units from these regions display similar stratigraphic and petrological evolution during the narrow window of activity (44.4–44.8 Ma), which is constrained by Ar–Ar dating. The lower parts of the volcano-stratigraphic sections contain hawaiite, and trachybasalts that have a mildly alkaline, nepheline-normative character (V1a subseries), together with clinopyroxene-hornblendite xenoliths. The middle portions of the sections contain basaltic andesitic to dacitic lavas that become tholeiitic/calc-alkaline in character (V1b subseries). In the middle to upper parts of the successions, tholeiitic/calc-alkaline basaltic andesite (V2a subseries) and nepheline-normative mildly alkaline basalts (V2b subseries) become dominant, marking the end of the volcanic episode. All of these units display negative high field strength element values, and enriched large-ion lithophile and light rare earth element values, which mimic subduction-related signatures. The Na-rich character, high Ba/Rb and low Rb/Sr ratios, together with FC3MS values (wt.% FeO/CaO-3 * MgO/SiO2 ), of these series indicate the presence of amphibole and pyroxene minerals in the source area. Also, Dy/Yb values from the most basic suites, V1a and V2b, are supportive of a spinel-bearing source area. Low-degree partial melting (∼1–5%) modelling of cumulate clinopyroxene-hornblendite xenoliths in the lava series provided the observed geochemical patterns in our most basic lava samples. Petrological observations indicate that the V1a and V1b subseries were shaped by fractional crystallization and assimilation-related modifications. In addition, the V2a subseries displays basic magma replenishment, with inversed clinopyroxene cores and mantle/rim transects. The V2b subseries were most likely shaped by fractional crystallization of homogenized basic magma mush. Post-collisional magmatism across the region was therefore generated by thinning of the lithospheric mantle during the middle Eocene.